The Existence of Sekapur Sirih Dance in Sungai Pinang Village, Hulu Kuantan Sub-District, Kuantan Singingi District - Desfiarni; Hayatun Ridha (Universitas Negeri Padang, 2024)
This study aims to describe the existence of Sekapur Sirih Dance in Sungai Pinang Village, Hulu Kuantan District, Kuantan Singingi Regency. This type of research is qualitative research with descriptive methods. The instrument in this research is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data collection techniques are done by means of literature study, observation, interviews and documentation. The steps of analysing data are data reduction and data display. The results showed that the existence of Sekapur Sirih Dance in Sungai Pinang Village experienced ups and downs in its activity in 2004 and also the years after that caused by the lack of funding from Sungai Pinang Village and local government to carry out the Pacu Jalur Culture, therefore the Pacu Jalur Culture was transferred to a district closer to Hulu Kuantan District, namely Kuantan Mudik District. And also caused by the entry of the times and new technology. In 2014 Sekapur Sirih Dance revived because it was asked by the Head of Sungai Pinang Village to perform at the opening of the Pacu Jalur Culture. Factors that influence the ebb and flow of Sekapur Sirih Dance are due to the lack of funding available and also due to the entry of the times and IPTEK. The effort to see the existence of Sekapur Sirih Dance in Sungai Pinang Village aims to inform the community that the ups and downs of Sekapur Sirih Dance occur due to several things. So that from what has happened the community can change their mindset to jointly revive and preserve Sekapur Sirih Dance as a Tradition Dance in Sungai Pinang Village.